Penyelenggaraan Pemerintah Negeri di Pulau Ambon Kabupaten Maluku Tengah Pasca Berlakunya Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Natanel Lainsamputty (SASI, 2019)
The purpose of this research is to analyze the state regulation in Ambon Island, Central Maluku Regency, to analyze the state Regulation after the enforcement of Act Number 6 of 2014 and analyze why the State is positioned as Adat Law on village administration in Ambon Island, Central Maluku Regency. This research is a normative-empirical legal research using secondary data type that covering three legal materials (primary, secondary and tertiary legal materials) and primary data obtained through interviews of respondents and interviewees. The results of this research indicate the first of the existence of government Negeri in the three districts of Leihitu District, Leihitu West District, and Salahutu District at the Central Maluku Regency in its regulation on pre-independence regime retained the original autonomy of the Negeri, but in the post-regime of the Negeri experienced various shifts State intervention is very dominant. Second, the State Regulation on Act Number 6 of 2014 must go through the process of inventory and classification of the existence of the State and determined by the Regional Regulation. Third, the position of the State in the Indonesian state administration system is Adat Law which has the right of autonomy to exercise power as a local self-governing community and local self governing.